Program Memutus Rantai Covid 19 Melalui Berwudhu Sebelum Belajar di Pondok Pesantren Darussalam Sumbersari Kencong Kepung Kediri - Moh Syukron Roziqin; Wildan Habibi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Religious education activities located in darussalam sumbersari boarding school can be a reference for the community about the importance of maintaining wudhu, because wudhu is also believed to eliminate the covid 19 virus, one of which is through hand washing. Based on this context, the habituation effort program before studying in this hut needs to be implemented and directed to provide prevention of covid 19 for students. This is seen as quite successful to resuscitate the santri about the rampant condition of covid 19 that is spreading in various countries. In an effort to break the covid 19 chain also raised good cooperation and communication between researchers and teachers and the role of students who are active in succeeding the program. The success of this program can also be used as a model of implementing religious reinforcement elsewhere by adjusting the existing context.